2008
DOI: 10.1159/000151246
|View full text |Cite
|
Sign up to set email alerts
|

Computer-Based Visual Evaluation as a Screening Tool after Intravitreal Injections of Vascular Endothelial Growth Factor Inhibitors

Abstract: Purpose: To evaluate the visual acuity (VA) of patients following intravitreal (IVT) injections. Methods: 15 patients received 3 anti-vascular-endothelial-growth-factor (VEGF) injections on a monthly basis. Prior to each injection as well as 2 months after, the patients received a standardized examination including Snellen VA and optical coherence tomography (OCT). During this time the patients were trained to evaluate their central VA by 3 computer-based tests: (a) VA was examined by the patient on a computer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 30 publications
0
3
0
1
Order By: Relevance
“…A similar study included patients with a duration of symptoms of up to 12 months, another analysis involved patients up to 3 months after initial diagnosis of NV-AMD [6,7]. Recently developed diagnostic techniques, which are based on the patients’ active participation as well as standardized and optimized documentation of key parameters, are important innovations in order to detect changes in vision as early as possible [30,31]. We chose a 6-month period, since a symptom interval that is shorter than 3 months does not comply with the practical experience of patient care, and since it is difficult to attribute a period to an acute event which lasts for more than 6 months.…”
Section: Discussionmentioning
confidence: 99%
“…A similar study included patients with a duration of symptoms of up to 12 months, another analysis involved patients up to 3 months after initial diagnosis of NV-AMD [6,7]. Recently developed diagnostic techniques, which are based on the patients’ active participation as well as standardized and optimized documentation of key parameters, are important innovations in order to detect changes in vision as early as possible [30,31]. We chose a 6-month period, since a symptom interval that is shorter than 3 months does not comply with the practical experience of patient care, and since it is difficult to attribute a period to an acute event which lasts for more than 6 months.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we suggest that MacuFix® has the potential to serve as a cost-effective home monitoring solution that can connect patients or individuals at risk for macular disease with their eye care professionals and thus improve patient self-management. As early as 2008, Meyer et al observed in a pilot study in 15 patients a good correlation between the standard examination including BCVA and OCT and a computer-based assessment of central vision, subjective categorization of their visual acuity development, and a digital marking of the metamorphopsia area [ 28 ]. In a larger group of 1444 patients, the paper-based ACTO self-test consisting of a reading chart gradated in decimal steps and six questions regarding the quality of the Amsler grid was accompanied by telephone contact with a coordinating center.…”
Section: Discussionmentioning
confidence: 99%
“…If diagnosed too late, it can cause irreparable eye damage. Fortunately AMD can be diagnosed with simple tests, even in the absence of medical staff [2]. These simple tests are offered by some smartphone and tablet applications, which can help to diagnose or at least indicate AMD and other eye diseases even at home.…”
Section: Introductionmentioning
confidence: 99%